PENGARUH AUDIT INTERNAL DALAM MENGELOLA RISIKO KEPATUHAN TERHADAP PROGRAM CORPORATE SOCIAL RESPONBILITY (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Sektor Perbankan 2019-2023) - Safira Dyah Cahyani; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
The purpose of this research is to examine the effect of internal audit on Corporate Social Responsibility (CSR) disclosure, with compliance risk as a mediating variable. There are two main variables in this research: internal audit as the independent variable and CSR disclosure as the dependent variable, with compliance risk acting as an intervening (mediating) variable.This study used banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023, with a total sample of 235 observations. Sampling was conducted using a purposive sampling method based on predetermined criteria. The analysis technique used in this research is multiple linear regression and Sobel test for mediation analysis.The results of this study indicate that internal audit has a positive and significant effect on CSR disclosure, while compliance risk does not have a significant effect and fails to mediate the relationship between internal audit and CSR disclosure.